Large-aperture alumina carrier as well as preparation method and application thereof

By adding inert fibers and dry materials of ammonium aluminum carbonate under low water powder conditions, special molding and calcining processes are carried out to prepare large-pore alumina carriers, which solves the problem of difficult to prepare carriers with pores greater than 500nm in the prior art, and achieves efficient hydrode-metallation and demetalization effect of residual oil.

CN119838586APending Publication Date: 2025-04-18REZEL ENGINEERING CORP

Patent Information

Application Number
CN202510085876.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to prepare alumina carriers with pores greater than 500 nm and pore distribution with a high proportion of pore distribution under low water powder ratio, which cannot meet the processing needs of high metal residues.

Method used

Large pore alumina support was prepared by adding inert fibers, aluminum hydroxide and ammonium aluminum carbonate to the dry material, and extruding, health, drying and calculating under low water powder ratio and high extrusion pressure.

Benefits of technology

Under the conditions of low gouache ratio, the volume proportion of pores greater than 500nm was successfully increased to 15-25%, meeting the demand for demetallic catalysts for high metal residues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838586A_ABST
    Figure CN119838586A_ABST
Patent Text Reader

Abstract

The invention provides a large-aperture alumina carrier as well as a preparation method and application thereof. The large-aperture alumina carrier is prepared from dry materials and water, and the dry materials comprise inert fibers, aluminum hydroxide and ammonium aluminum carbonate. According to the invention, under the condition of low water-powder ratio, primary pores and secondary accumulation pores in aluminum hydroxide and ammonium aluminum carbonate are reserved to the greatest extent under high extrusion pressure in the carrier extrusion and molding process due to the enhancement effect of inert fibers; although the apertures of the primary pores, the secondary accumulation pores and the macropores generated by decomposition of the ammonium aluminum carbonate are reduced during roasting of the carrier, the volume ratio of the pores with the pore size of more than 500nm in the final carrier is still obviously increased due to the existence of the inert fibers, and the volume ratio of the pores with the pore size of more than 500nm is 15-25%. In addition, the by-product ammonium aluminum carbonate generated in the recovery process of the waste ethylene oxide catalyst is used as the raw material and the macroporous pore-enlarging agent, so that the production cost of the large-aperture alumina carrier is reduced. The prepared large-aperture alumina carrier can be used for preparing a residual oil hydrodemetallization catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for residual oil hydroprocessing, and in particular to a large-pore alumina carrier, a preparation method of the large-pore alumina carrier and an application of the large-pore alumina carrier. Background Art

[0002] As crude oil production grows slowly and becomes increasingly heavier, as well as the market demand for light oil products continues to increase, coupled with increasingly stringent environmental regulations, the residual oil processing capacity has grown rapidly, especially the fixed-bed residual oil hydroprocessing technology has developed the fastest.

[0003] Fixed-bed residue oil hydroprocessing technology uses hydrogen as a catalyst to carry out hydrogenation reaction on residue oil, mainly through demetallizing agents, desulfurizing agents and residual carbon removal catalysts to convert heavy components such as high sulfur, high nitrogen and high metals into light products with low sulfur, low nitrogen and low metals.

[0004] The main function of demetallization catalyst is to remove metal impurities from residual oil. Due to the high density and viscosity of residual oil raw materials, it is not conducive to the diffusion of residual oil raw materials in the pores of residual oil hydroprocessing catalysts. In particular, macromolecular substances such as colloids and asphaltene in the raw materials cannot enter the micropores of the demetallization agent and cannot be converted into small molecular substances. This not only affects the impurity removal rate in the residual oil hydrogenation reaction, but also affects the service life and operational stability of the catalyst. Therefore, it is necessary to develop a new demetallization catalyst with a pore size of >100nm.

[0005] At present, the carrier of the demetallization catalyst is made of alumina material. A large-pore alumina carrier is obtained by adding a pore-expanding template agent to alumina and calcining.

[0006] For example, the Chinese patent with publication number CN105983443A discloses a bimodal pore structure alumina carrier and a preparation method thereof, wherein the bimodal pore alumina carrier is prepared by using the chemical pore expander boric acid and the organic pore expander polyvinyl alcohol, wherein the pores with a pore size of 100-2000nm account for 24.1%. The Chinese patent with publication number CN107913691A discloses a macroporous alumina carrier and a preparation method thereof, wherein the preparation method prepares a macroporous alumina carrier by adding styrene-butadiene rubber emulsion as a pore expander, wherein the pore size distribution of the alumina carrier is 60-200nm and the macropore ratio is 2-70%. The Chinese patent with publication number CN108236939A discloses a mesoporous / macroporous alumina carrier and a preparation method thereof, wherein the preparation method obtains a mesoporous / macroporous alumina carrier by adding nitrile rubber emulsion as a pore expander, wherein the pore size of the carrier is 100-200nm and the macropore ratio is 50-90%.

[0007] The above patent can prepare a carrier rich in pores greater than 100nm by adding a macropore expander, which meets the demand for preparing catalysts for crude oil processing with nickel content of more than 100μg / g in Gaosheng crude oil in North China and Dongjiang crude oil in Xinjiang Uygur Autonomous Region. However, for high-metal residue oils, such as vacuum residue oils of Iranian Sili, Iranian light and Iranian heavy crude oils, and atmospheric residue oils of Mexican Maya crude oil and Canadian Cold Lake crude oil, the metal content exceeds 200μg / g, and the metal content of vacuum residue oil of Mexican Maya crude oil is as high as more than 800μg / g. It is difficult for a carrier with only macropores greater than 100nm to meet the application requirements. Therefore, an alumina carrier with a larger pore size is required.

[0008] Usually, macropores larger than 500nm are more suitable as diffusion holes for demetallization agents. At present, the reason why the proportion of pores >500nm is low when a single macropore pore expander is used to prepare alumina carriers is that the high-temperature sintering and high extrusion pressure during the molding process cause the macropores to collapse into mesopores, and the mesopores to collapse into small pores. It is generally believed that the higher the calcination temperature, the stronger the sintering effect. For demetallization agent carriers, the macropore content itself is high and the packing density will be reduced. Therefore, in order to compensate for the packing density, the bulk density of the carrier will be increased, which will cause the feed water-powder ratio to decrease, the extrusion molding pressure to increase, and the stacking channels between the alumina raw material powder particles to collapse, and the proportion of macropores will be further reduced. Therefore, it is necessary to seek an alumina carrier that can still prepare pores larger than 500nm and a high pore distribution ratio under the conditions of low water-powder ratio and high extrusion pressure. Summary of the invention

[0009] The present invention aims to solve the problem in the prior art that it is difficult to prepare an alumina carrier with pores larger than 500 nm and a high pore distribution ratio under low water-powder ratio conditions, and proposes a large-pore alumina carrier and its preparation method and application.

[0010] The technical method of the present invention is as follows:

[0011] The invention discloses a macroporous alumina carrier, which is prepared from dry materials and water. The dry materials include inert fiber, aluminum hydroxide and ammonium aluminum carbonate.

[0012] Specifically, the BET (gas adsorption) pore volume of the large-pore alumina carrier is 0.60-0.80 mL / g, the pore volume of 100-500 nm accounts for 10-20% of the total pore volume, and the pore volume above 500 nm accounts for 15-25% of the total pore volume.

[0013] Specifically, the inert fiber is basalt fiber and / or alkali-free chopped glass fiber with a length of 3-5 mm, wherein the inert basalt fiber is high temperature resistant basalt fiber (heat resistant type) in the standard "Classification, Grading and Code of Basalt Fiber" (GB / T 38111-2019), with classification code BTR, grading code BTRI and BTRII.

[0014] Optionally, inert fibers are added in an amount of 5-15%.

[0015] Specifically, the ammonium aluminum carbonate is derived from a by-product produced during the recovery process of waste ethylene oxide catalyst; the ammonium aluminum carbonate is in the form of powder or filter cake, preferably filter cake.

[0016] Optionally, the amount of ammonium aluminum carbonate added is 20-50%.

[0017] Furthermore, the dry material also contains sesbania powder and / or guar gum powder.

[0018] Furthermore, the dry material also contains cellulose, wherein the cellulose is one or more of hydroxypropyl methylcellulose, carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.

[0019] Furthermore, the dry material and water also contain acid; wherein the acid includes an organic acid or an inorganic acid, the organic acid includes one or more of citric acid, oxalic acid, and acetic acid, and the inorganic acid includes one or two of nitric acid and phosphoric acid.

[0020] The present invention also provides a method for preparing a large-pore alumina carrier, which comprises: kneading raw materials and water, forming, curing, drying and calcining to obtain the large-pore alumina carrier.

[0021] Specifically, the curing temperature is 20-40°C, and the curing time is greater than 4 hours; the drying temperature is 100-120°C, and the drying time is 1-3 hours; the roasting temperature is 850-950°C, and the roasting time is 2-4 hours.

[0022] The present invention also provides an application of a large-pore alumina carrier, wherein the large-pore alumina carrier is applied in a residual oil hydrodemetallization catalyst, and the large-pore alumina carrier is the large-pore alumina carrier described above or the large-pore alumina carrier prepared by the above preparation method.

[0023] The beneficial effects of the present invention are:

[0024] In the process of extrusion and molding under low water-powder ratio, due to the reinforcing effect of inert fibers, the primary pores and secondary stacked pores in aluminum hydroxide and ammonium aluminum carbonate are retained to the maximum extent under high extrusion pressure; although the pore diameters of the primary pores, secondary stacked pores and macropores generated by decomposition of ammonium aluminum carbonate will be reduced when the carrier is roasted, due to the presence of inert fibers, the volume proportion of pores with a size of 500 nm or more in the final carrier is significantly increased, wherein the volume proportion of pores with a size of 500 nm or more is 15-25%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The nitrogen adsorption-desorption curve and pore distribution diagram of the finished carrier of Example 1;

[0026] Figure 2 The mercury intrusion pore distribution diagram of the carrier of Examples 1 and 2;

[0027] Figure 3 This is the mercury intrusion pore distribution diagram of the carriers of Comparative Examples 3 and 4. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The idea of ​​the present invention is to design a demetallized catalyst carrier, which, firstly, can have a relatively large pore size (>500nm) and a high pore distribution ratio under a low water-powder ratio (the ratio of water in the feed to the final product (aluminum hydroxide converted to the finished product + ammonium aluminum carbonate converted to the finished product)), secondly, the product price is moderate and highly competitive, and thirdly, the preparation process is simple.

[0030] Therefore, the present invention provides a large-pore alumina carrier composed of raw materials and water, which is prepared from dry materials and water, and the dry materials include inert fibers, aluminum hydroxide and ammonium aluminum carbonate.

[0031] Specifically, aluminum hydroxide can be a powder, and the aluminum hydroxide powder has a BET pore volume>1.0mL / g, and a nitric acid peptization index of 15-40%. Preferably, the nitric acid peptization index is 25-35%. Here, the aluminum hydroxide raw material powder of the residual oil hydrogenation catalyst of the present invention usually has a BET pore volume>1.0mL / g, so that the BET pore volume of the carrier is not less than 0.60mL / g, thereby improving the hydrogenation demetallization ability of the finished catalyst. The peptization index of the present invention is 25-35%, and the crushing strength of the final alumina carrier can meet the product index without using an organic acid or an inorganic acid as a peptizing agent.

[0032] Specifically, the inert fiber is basalt fiber and / or alkali-free short glass fiber, with a length of 3-5 mm. Here, when the length is less than 3 mm, the supporting effect is insufficient, and when the length is greater than 5 mm, it is not conducive to extrusion molding, and the finished product has floating fibers and is easy to block the extrusion module. Preferably, the basalt fiber is selected from high temperature resistant basalt fiber (heat resistant type); alkali-free short glass fiber, R 2 O<0.8%. Here, since both the high temperature resistant basalt fiber and the alkali-free chopped glass fiber have high temperature resistance and good supporting properties, they have good stability under high temperature roasting environment and can be used as proppants.

[0033] The present invention adds an appropriate proportion (5-15%) of inert fibers to the raw materials. Under low water-powder ratio conditions, during the extrusion and molding process, due to the reinforcing effect of the inert fibers, the primary pores and secondary stacked pores in the dry material (aluminum hydroxide, ammonium aluminum carbonate) can be supported, and these pores are retained to the maximum extent under high extrusion pressure. When the carrier dry strips are calcined, although the pore diameter will be reduced, in the presence of the inert fibers, the proportion of the reduced pores above 500 nm is significantly increased.

[0034] Specifically, ammonium aluminum carbonate is derived from a byproduct produced in the process of recovering waste ethylene oxide catalysts, and the form of ammonium aluminum carbonate is filter cake or powder. Preferably, the form is filter cake. The amount of ammonium aluminum carbonate added is 20-50%. Ammonium aluminum carbonate can be used as an aluminum source and a pore expander at the same time, because the decomposition of ammonium aluminum carbonate can produce a large amount of gas, thereby playing a role in expanding the pores, replacing the more expensive organic polymer macroporous pore expander; at the same time, ammonium aluminum carbonate can be recovered from the ammonium aluminum carbonate filter cake produced by the waste catalyst, further saving costs.

[0035] The present invention uses primary pores and secondary stacked pores generated by the decomposition of aluminum hydroxide and ammonium aluminum carbonate, and by adding inert fibers, the collapse and sintering of the above-mentioned macropores can be alleviated under low water-powder ratio and high extrusion pressure, and the proportion of pores >500nm is increased. The BET pore volume of the macroporous alumina carrier of the present invention is 0.60-0.80mL / g, the pore volume of 100-500nm accounts for 10-20% of the total pore volume, and the pore volume above 500nm accounts for 15-25% of the total pore volume.

[0036] In one embodiment, inert fiber, ammonium aluminum carbonate and aluminum hydroxide powder are used as dry materials, and the dry materials are calculated by mass fraction, inert fiber is 5-15%, ammonium aluminum carbonate is 20-50%, and aluminum hydroxide powder is the balance. Here, an appropriate amount of water can be added. Here, the water can be deionized water.

[0037] In one embodiment, the dry material further comprises sesbania powder and / or guar gum powder, preferably sesbania powder. The sesbania powder acts as an extrusion aid and lubricant, making the extrusion molding process smoother.

[0038] In one embodiment, the dry material also contains cellulose, wherein the cellulose is one or more of hydroxypropyl methylcellulose, carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose. Here, the binder mainly serves to bind the various substances to ensure that the materials do not become loose during molding.

[0039] In one embodiment, the dry material and water also contain acid. Wherein, the acid includes organic acid or inorganic acid, the organic acid includes one or more of citric acid, oxalic acid, and acetic acid, and the inorganic acid includes one or two of nitric acid and phosphoric acid. Here, the acid mainly plays a role of peptization. If the above materials can achieve good peptization, it can be selected not to add. However, in order to eliminate the influence of fluctuations in raw material indicators (especially peptization index), it is necessary to add a small amount of acid to stabilize production. Here, the acid can be used with deionized water solution.

[0040] In one embodiment, taking aluminum hydroxide, ammonium aluminum carbonate, inert fiber, sesbania, cellulose, acid and deionized water as examples, by mass, aluminum hydroxide is 700-1200 parts, ammonium aluminum carbonate is 400-100 parts, inert fiber is 60-80 parts, sesbania is 40-80 parts, cellulose is 10-30 parts, acid is 10-30 parts, and water is 1600-1800 parts.

[0041] The present invention also provides a method for preparing a large-pore alumina carrier, which comprises: kneading dry materials and water, forming, curing, drying and calcining to obtain a large-pore alumina carrier.

[0042] In one embodiment, the curing temperature is 20-40° C. and the curing time is greater than 4 hours. The curing process allows the dry material, additives and water to fully react, preventing subsequent drying and roasting processes from causing cracks and strength reduction.

[0043] In one embodiment, the drying temperature is 100-120° C. and the drying time is 1-3 hours. Here, the drying process is carried out by heating to remove the moisture in the wet strips to obtain dry strips, fix the shape of the dry strips, and prevent deformation caused by stretching and extrusion, which affects the quality of the final catalyst.

[0044] In one embodiment, the calcination temperature is 850-950°C and the calcination time is 2-4 hours. Here, the temperature rise process removes moisture, removes various additives (inert fiber, sesbania powder and / or guar gum powder, cellulose), peptizer (acid) and begins to decompose the pore expander (ammonium aluminum carbonate), and the temperature continues to rise, aluminum hydroxide and ammonium aluminum carbonate are pyrolyzed to generate γ-alumina; a phase change occurs at high temperature to obtain the final θ-alumina carrier.

[0045] In one embodiment, the molding is performed by extrusion molding. Preferably, a high extrusion pressure is used. Here, the high extrusion pressure can correspond to the bulk density, and the bulk density can be corresponded to the feed dry basis. Here, when filter cake is used as the raw material, it is not appropriate to use the water-powder ratio for investigation. Therefore, the present invention uses the feed dry basis to replace the water-powder ratio. The lower the water-powder ratio and the higher the feed dry basis, the lower the moisture content and the drier the material, the greater the extrusion pressure and the more difficult the molding. For example, feed dry basis = finished product mass / total feed mass. When the feed dry basis is high, the moisture content is low, the water-powder ratio is low, and the extrusion pressure naturally increases.

[0046] Taking the water-powder ratio as an example, in the prior art, when the water-powder mass ratio is <1.70, that is, the feed dry basis is >29% (assuming that all aluminum hydroxide powder is used as raw material), pores larger than 500nm collapse and have a low proportion due to the absence of proppant (inert fiber). If proppant (inert fiber) is added, the proportion of pores larger than 500nm can be significantly increased.

[0047] Taking bulk density as an example, when the bulk density is 0.40g / mL, a relatively high macropore (>500nm) pore volume ratio can be achieved. However, when the bulk density is 0.48g / mL, due to the reduction of water input and the significant reduction in the water-powder ratio, the material becomes dry, the extrusion pressure increases, and in the absence of a proppant (inert fiber), the pores are squeezed and collapsed, resulting in a relatively large loss of pores >500nm. In actual application, a carrier with a relatively high bulk density is required, which is difficult to meet with the prior art. The present invention can still achieve a relatively high macropore (>500nm) pore volume ratio under the condition of the presence of an inert fiber proppant and under high extrusion pressure (higher bulk density, low water-powder ratio).

[0048] The present invention also provides an application of a large-pore alumina carrier, which is used in a residue oil hydrodemetallization catalyst. The large-pore alumina carrier is the large-pore alumina carrier mentioned above or a large-pore alumina carrier prepared by the above-mentioned preparation method.

[0049] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0050] Example 1

[0051] This embodiment provides a method for preparing a large-pore alumina carrier, the preparation method comprising the following steps:

[0052] 1050g of aluminum hydroxide powder (burning residue 66.67%, pore volume 1.20mL / g, peptization index 26%), 417g of ammonium aluminum carbonate powder (burning residue 72.00%), 70g of alkali-free chopped glass fiber (length 3-5mm), 25g of sesbania powder, and 50g of hydroxypropyl methylcellulose were mixed for 10min, and then an acid solution containing 20g of acetic acid and 1700g of water was added, and kneaded for 25min, and then Extrusion was performed on an extruder with a module size of 1.90*1.70 mm, an extrusion frequency of 15 Hz, curing at room temperature for 12 h, drying at 110°C for 2 h, and calcining at 930°C for 4 h to obtain a large-pore alumina carrier C1. Figure 1 As shown, the nitrogen adsorption-desorption curve and pore distribution diagram of the finished carrier of Example 1.

[0053] Here, the dry basis and water-powder ratio of the feed materials are as follows.

[0054]

[0055]

[0056] Here, the ignition residues of aluminum hydroxide powder and ammonium aluminum carbonate are the weight percentages of the residues after heat treating the sample at 600°C for 2 hours; the total mass of aluminum oxide in the feed (or finished product) is 1000g, that is, 700g (1050g×66.67%) of aluminum oxide in aluminum hydroxide powder and 300g (417g×72.00%) of aluminum oxide in ammonium aluminum carbonate powder, the same below.

[0057] Example 2

[0058] This embodiment provides a method for preparing a large-pore alumina carrier, the preparation method comprising the following steps:

[0059] 1125g of aluminum hydroxide powder (burning residue 66.67%, pore volume 1.20mL / g, peptization index 26%), 916g of ammonium aluminum carbonate filter cake (burning residue 27.30%), 70g of alkali-free chopped glass fiber (length 3-5mm), 20g of sesbania powder, and 40g of hydroxypropyl methylcellulose were mixed for 15min, and then an acid solution containing 10g of acetic acid and 1174g of water was added, and kneaded for 20min, and then Extrusion was performed on an extruder with a module size of 1.90*1.70 mm, an extrusion frequency of 18 Hz, curing at room temperature for 10 h, drying at 105 °C for 4 h, and calcination at 930 °C for 3 h to obtain a large-pore alumina carrier C2. Figure 2 As shown, the mercury intrusion pore distribution diagram of the carrier of Examples 1 and 2.

[0060] Here, the dry basis and water-powder ratio of the feed materials are as follows.

[0061]

[0062] The free water in the ammonium aluminum carbonate filter cake is included in the feed.

[0063] Example 3

[0064] This embodiment provides a method for preparing a large-pore alumina carrier, the preparation method comprising the following steps:

[0065] 900 g of aluminum hydroxide powder (burning residue 66.67%, pore volume 1.20 mL / g, peptization index 26%), 556 g of ammonium aluminum carbonate powder (burning residue 72.00%), 100 g of alkali-free chopped glass fiber (length 3-5 mm), 20 g of sesbania powder, and 60 g of hydroxypropyl methylcellulose were mixed for 10 min, and then an acid solution containing 20 g of acetic acid and 1700 g of water was added, and kneaded for 25 min, and then Extruded on an extruder, the module size is a four-leaf clover 1.90*1.70mm, the extrusion frequency is 18Hz, cured at room temperature for 6h, dried at 120℃ for 2h, and calcined at 930℃ for 2h to obtain a large-pore alumina carrier C3.

[0066] Here, the dry basis and water-powder ratio of the feed materials are as follows.

[0067]

[0068]

[0069] Example 4

[0070] This embodiment provides a method for preparing a large-pore alumina carrier, the preparation method comprising the following steps:

[0071] Take 752g aluminum hydroxide powder (burning residue 66.50%, pore volume 1.02mL / g, peptization index 21%), 694g aluminum ammonium carbonate powder (burning residue 72.00%), high temperature resistant basalt fiber (heat resistant type) (length 3-5mm) 120g, 10g sesbania powder, 70g hydroxypropyl methylcellulose and mix for 5min, then add acid solution containing 25g acetic acid and 1684g water, knead for 25min, and then Extruded on an extruder, the module size is a four-leaf clover 1.90*1.70mm, the extrusion frequency is 18Hz, cured at room temperature for 4h, dried at 120℃ for 4h, and calcined at 930℃ for 3h to obtain a large-pore alumina carrier C4.

[0072] Here, the dry basis and water-powder ratio of the feed materials are as follows.

[0073]

[0074] Comparative Example 1

[0075] The difference from Example 1 is that no alkali-free chopped glass fibers are added, and the obtained alumina carrier is recorded as C5.

[0076] Comparative Example 2

[0077] Referring to the method disclosed in CN105983443A, polyvinyl alcohol and boric acid are used as pore-enlarging agents, specifically:

[0078] 1500g aluminum hydroxide powder (burning residue 66.67%, pore volume 1.20mL / g, peptization index 20%), 50g sesbania powder, 25g hydroxypropyl methylcellulose, 100g polyvinyl alcohol were mixed for 5min, then an acid solution containing 40g anhydrous boric acid, 10g acetic acid and 1700g water was added, kneaded for 10min, and then Extruded on an extruder, the module size is a four-leaf clover 1.90*1.70mm, the extrusion frequency is 12.5Hz, cured at room temperature for 5h, dried at 120℃ for 2h, and calcined at 930℃ for 4h to obtain the carrier C6.

[0079] Comparative Example 3

[0080] The difference from Example 1 is that ordinary 80-mesh alkali-free glass fiber powder is used instead of the alkali-free chopped glass fiber, and the obtained carrier is recorded as C7.

[0081] Comparative Example 4

[0082] The difference from Example 1 is that polypropylene chopped fibers are used instead of alkali-free chopped glass fibers, and the obtained carrier is denoted as C8. Figure 3 As shown, the mercury intrusion pore distribution diagram of the carrier of Comparative Examples 3 and 4.

[0083] The results are shown in Table 1.

[0084] Table 1 Carrier pore structure properties

[0085]

[0086] From the mercury intrusion pore distribution data (C5 and C6) of Comparative Examples 1 and 2, it can be seen that without the addition of inert fibers, the proportion of pores > 500nm in the finished carrier is very small; the mercury intrusion pore distribution data of the carriers prepared in Comparative Examples 1 and 2 are comparable, indicating that the performance of ammonium aluminum carbonate as a pore expander is comparable to that of a polymer organic pore expander. From the mercury intrusion pore distribution data (C7 and C8) of Comparative Examples 3 and 4, it can be seen that the proportion of pores > 500nm in the finished carrier is also very small. The main reason is that the glass fiber powder cannot play an effective supporting role due to its disordered distribution, anisotropy and lower than the "critical length", resulting in a low proportion of pores > 500nm; and the PP (polypropylene) chopped fibers decompose during the high-temperature roasting process and cannot support large pores, resulting in a low proportion of pores > 500nm.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A large-pore alumina carrier, characterized in that: It is prepared from dry materials and water. The dry materials include inert fibers, aluminum hydroxide and ammonium aluminum carbonate.

2. The macroporous alumina carrier according to claim 1, characterized in that: The BET pore volume of the large-pore alumina carrier is 0.60-0.80 mL / g, the pore volume of 100-500 nm accounts for 10-20% of the total pore volume, and the pore volume above 500 nm accounts for 15-25% of the total pore volume.

3. The macroporous alumina carrier according to claim 1, characterized in that: The inert fiber is basalt fiber and / or alkali-free chopped glass fiber, and the length is 3-5 mm; The added amount of the inert fiber is 5-15%.

4. The macroporous alumina carrier according to claim 1, characterized in that: The ammonium aluminum carbonate is derived from a byproduct produced during the recovery process of waste ethylene oxide catalyst; The ammonium aluminum carbonate is in the form of powder or filter cake, preferably filter cake; The addition amount of the ammonium aluminum carbonate is 20-50%.

5. The macroporous alumina carrier according to claim 1, characterized in that: The dry materials also include sesbania powder and / or guar gum powder.

6. The macroporous alumina carrier according to claim 1, characterized in that: The dry material also contains cellulose, wherein the cellulose is one or more of hydroxypropyl methylcellulose, carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.

7. The macroporous alumina carrier according to claim 1, characterized in that: The dry material and water also contain acid; wherein the acid comprises an organic acid or an inorganic acid, the organic acid comprises one or more of citric acid, oxalic acid, and acetic acid, and the inorganic acid comprises one or two of nitric acid and phosphoric acid.

8. The method for preparing a large-pore alumina carrier according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The dry material and water are kneaded, formed, cured, dried and calcined to obtain a large-pore alumina carrier.

9. The preparation method according to claim 8, characterized in that: The curing temperature is 20-40°C, and the curing time is greater than 4 hours; The drying temperature is 100-120°C and the drying time is 1-3h; The calcination temperature is 850-950° C., and the calcination time is 2-4 hours.

10. An application of a large-pore alumina carrier, characterized in that: The large-pore alumina carrier is used in a residue oil hydrodemetallization catalyst, and the large-pore alumina carrier is the large-pore alumina carrier described in any one of claims 1 to 7 or the large-pore alumina carrier prepared by the preparation method described in any one of claims 8 to 9.

Citation Information

Patent Citations

  • Double-peak-pore-structured aluminum oxide supporter and preparation method thereof

    CN105983443A

  • Macropore alumina carrier and preparation method thereof

    CN107913691A

  • Mesoporous / macropore-containing alumina carrier and preparation method thereof

    CN108236939A

Cited By

  • Gasoline pre-hydrogenation tooth spherical alumina carrier and preparation method thereof

    CN121819797A

  • Preparation method of high-bulk-ratio double-peak pore-tooth spherical alumina carrier

    CN121819800A

  • A method for preparing a high bulk dual-peak dentrite spherical alumina carrier

    CN121819800B